Analysis of the dynamics of competitive positions of national economy sectors in world markets - Kovalev, Mikhail M.; Koroleva, Anna A.; Jian, Tang (Journal of the Belarusian State University. Economics, 2022)
The article proposes a model of systematic analysis of the dynamics of countries economic competitive positions in global markets based on a set of complementary indicators, the most important of which are the dynamics of the global market share, the dynamics of net exports and its share in GDP, as well as the dynamics of the export-import coverage ratio (characterises how much income in foreign markets covers the payment of imports in domestic). The model is implemented in the methodology of analysis of export-import operations of a country for a specific group of goods (services). The application of the methodology is illustrated in two world markets – transport and computer services, which are important for the balance of payments of the trade in services of the Republic of Belarus.
Keywords: dynamics of competitive positions; export-import operations; economic growth